A inovação responsável como ferramenta de responsividade de PMEs em períodos de crise - Escalli, Lyon Heitor (Universidade do Vale do Rio dos Sinos, 2022)
In December 2019, China became the first country in the world to register the existence of cases of the new Coronavirus (Sars-CoV-2), and, a few months later, at the beginning of 2020, the World Health Organization declared an international public health emergency, officializing the COVID-19 pandemic; in a few days, the entire functional structure of society as we knew it underwent severe changes. Recent studies argue that the pandemic has become a period of self-reflection for humanity so that alternative and beneficial solutions may be adopted to make it possible to overcome the crisis. With the serious impact on the economic context, many organizations had to change their routines, and among those most affected by the new Coronavirus are the Small and Medium-sized Enterprises (SMEs). As they are more flexible and adaptive, the literature states that SMEs respond to unforeseen adversities through actions based on adaptation, responsiveness and resilience. Responsible Innovation is an approach that stands out for studying the innovation generated by organizations, the way they create value for themselves and also for society with long-term effects, taking into account the ethical and social aspects of the impacts caused by their activities. Dynamic Capabilities is a field that studies the way companies create, integrate and reconfigure their internal and external resources and competencies to meet the rapid changes that occur in different scenarios. This dissertation’s research question is to study how the microfoundations of Dynamic Capabilities can influence the responsiveness of SMEs in the industrial sector in times of crisis, through the theoretical lens of Responsible Innovation and Dynamic Capabilities. This dissertation has an exploratory character and was developed based on the case study of three small companies located in Brazil. The results obtained demonstrate that responsiveness is a higher order DC composed of four sub-capacities named Sensing (Anticipation), Learning (Reflexivity), Integration (Inclusion) and Reconfiguration; these sub-capacities are built through specific microfoundations created from the routine of SMEs and IT is a tool that enhances these elements’ responsiveness. Among the contributions made by this dissertation are: providing a conceptual theoretical model that identifies which microfoundations of Dynamic Capabilities were used by industrial SMEs during the COVID-19 crisis; analyze how these micro-foundations combine with the principles guided by Responsible Innovation focused on its responsiveness dimension; to show its relationship with responsiveness seen from the perspective of the Dynamic Capabilities literature; classify these micro-foundations into sub-capacities inherent to SMEs; establish a relationship between the micro-foundations developed by companies and the RI, and highlights the benefits that organizations can acquire by undertaking actions that take into account the ethics of their processes and their innovations; carry out research in SMEs, which need further studies on the implementation of RI in their context; highlight the importance of SMEs for the region where they are located; report how they built their plan of actions in the pandemic, and how these actions were implemented in their routines; present the final conceptual theoretical model aimed at helping SME managers to create and/or structure a crisis planning considering ethical, responsible and social innovative thinking, and also help public managers in the construction of social policies that are responsive to emerging issues in society .
Keywords: Inovação responsável; Capacidades dinâmicas; PMEs; Responsividade; Covid-19; Responsible innovation; Dynamic capabilities; SMEs; Responsiveness; ACCNPQ::Ciências Sociais Aplicadas::Administração